Government Efforts to Prevent Stunting in North Kelarik Village - Rispati, Meli; Inizawati, Inizawati (PT FORMOSA CENDEKIA GLOBAL, 2023)
A child is said to be stunted if his weight, height and slowness in thinking are not appropriate for his age. Stunting itself can be a factor in death due to inadequate nutrition so that the body's immune system is weak and susceptible to disease. The aim of this research is to find out the efforts made by the government in dealing with stunting cases in North Kelarik Village. In this research, we as researchers used the field research method, which is a research method that goes directly to the field. Field research is a type of research that studies phenomena in their natural environment. It was concluded that stunting in North Kelarik village in 2022 had decreased from the previous year, this was due to programs implemented by the government and the participation of residents so that stunting could decrease.